2020
DOI: 10.3846/jbem.2020.13195
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Performance on Payment Dynamics: Evidence From the Italian Manufacturing Industry

Abstract: This work aims to shed new light on the relation between institutional performance and firm dynamics. Considering the Italian manufacturing industry and a panel of 3 years, the authors investigate the relation between the time needed by courts to enforce debtors’ obligations and the time needed by enterprises to repay their debts. In particular, we test the hypothesis that efficiency in settling mortgage foreclosure and bankruptcy cases can affect the creditors’ decision making on judicial disputes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Moreover, adopting RE models, our hypothesis is once again confirmed (see Tables A3 and A4). Lastly, our results are coherent with the literature on the judiciary and firms' access to the capital market (Haselmann & Wachtel, 2010; Moro et al, 2018) and barriers to investments in environmental strategies (García‐Quevedo et al, 2020), as well as current evidence on the Italian manufacturing industry (Falavigna & Ippoliti, 2020, 2021b).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, adopting RE models, our hypothesis is once again confirmed (see Tables A3 and A4). Lastly, our results are coherent with the literature on the judiciary and firms' access to the capital market (Haselmann & Wachtel, 2010; Moro et al, 2018) and barriers to investments in environmental strategies (García‐Quevedo et al, 2020), as well as current evidence on the Italian manufacturing industry (Falavigna & Ippoliti, 2020, 2021b).…”
Section: Resultssupporting
confidence: 90%
“…This means that, anticipating that creditors will be unable to recover their loans easily and cheaply via the courts, borrowers are tempted to default, and lenders respond by reducing the availability of credit. Falavigna and Ippoliti (2018, 2020) gathered similar data on opportunistic behavior and came to the conclusion that the higher the judicial inefficiency in enforcing creditors' rights, the higher the risks taken by managers and/or stockholders, due to the perceived lower likelihood of creditors applying for a declaration of insolvency. Examining loan repayment delays in Italy, Schiantarelli et al (2020) confirmed this evidence, demonstrating that a firm's decision to delay payments to banks depends on its financial health and that legal enforcement of collateral recovery can amplify this phenomenon.…”
Section: Theoretical Background: Judicial Efficiency and Financial Dy...mentioning
confidence: 89%
See 1 more Smart Citation
“…This condition might be negatively amplified by asymmetric information between parties and moral hazards [6][7][8], which are even more significant if we consider SMEs, since the probability of being under financial constraint depends on a firm's size [9][10][11]. Therefore, it might prove too difficult or excessively costly for SMEs to finance investments and/or other managerial decisions using external resources and, consequently, companies could adopt internal resources if they are available [12,13] or, alternatively, trade credits [14][15][16][17]. Among managerial decisions, the payment of dividends represents one of the most important.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the performance is, also, impacted by the inventory holding strategies (Afrifa and Berchie 2019) and by the economic resource management (Maity et al 2019). In general, firms with higher levels of WC pay their liabilities over a shorter period (Falavigna and Ippoliti 2020). The WCM policies also impact the firm's ability to deal with adverse market cycles (Filbeck et al 2017).…”
Section: Working Capital Management Policiesmentioning
confidence: 99%